The Sport Specific Movement Assessment. What it is and how it can influence the training of Canada's high performance athletes - Craven, B. (High Performance SIRCuit, 2010)
Human performance is what defines sport as indicated by the Olympic motto of "Citius, Altius, Fortius". But it's not just about any movement. It's about precise movement. As the 2010 Winter Olympics and Paralympics come to a close we are once again reminded that high performance is not about being the best, but rather being the best on the day! As we prepare for the 2010 summer Olympics and 2014 winter Olympics the goal of every coach remains the same, be ready to be your best for those games on the day. One of the cornerstones of a best ever performance is precision movement and precise skill execution. The purpose of this article is to discuss how as a coach you can monitor movement patterns using a Sport Specific Movement Assessment (SSMA) as a means of detecting potential injuries as well as determining when training is altering movement patterns.